2021
DOI: 10.2147/ccid.s322530
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Alzheimer’s Disease and Skin Diseases: A Review

Abstract: Alzheimer’s disease is the most common type of dementia placing a heavy burden on the healthcare system worldwide. Skin diseases are also one of the most common health problems. Several skin diseases are associated with Alzheimer’s disease through different mechanisms. This review summarizes the relationship between Alzheimer’s disease and several types of skin diseases, including bullous pemphigoid, hidradenitis suppurativa, psoriasis, skin cancer, and cutaneous amyloidosis, and provides suggestions based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…Patients with Alzheimer's disease have significantly higher rates of autoantibody detection than controls 26 . Alzheimer's disease is epidemiologically associated with autoimmune diseases such as rheumatoid arthritis, 27 bullous pemphigoid, 28 pyogenic hidradenitis 28 and systemic lupus erythematosus 29 . The genetic loci associated with Alzheimer's disease include genes related to the immune system 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Alzheimer's disease have significantly higher rates of autoantibody detection than controls 26 . Alzheimer's disease is epidemiologically associated with autoimmune diseases such as rheumatoid arthritis, 27 bullous pemphigoid, 28 pyogenic hidradenitis 28 and systemic lupus erythematosus 29 . The genetic loci associated with Alzheimer's disease include genes related to the immune system 30 .…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that most studies support such a hypothesis, but of course, more studies are required for definite conclusions (Zhao et al, 2021 ). A review by Zhang et al introduced a hypothesis of a bidirectional link between psoriasis and AD: on one hand, psoriasis predisposes to AD, but on the other hand, AD patients may be at increased risk of psoriasis (Zhang et al, 2021 ). The authors justified the relationship between these two diseases by the common background: inflammatory, immunological, and genetic (Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A review by Zhang et al introduced a hypothesis of a bidirectional link between psoriasis and AD: on one hand, psoriasis predisposes to AD, but on the other hand, AD patients may be at increased risk of psoriasis (Zhang et al, 2021 ). The authors justified the relationship between these two diseases by the common background: inflammatory, immunological, and genetic (Zhang et al, 2021 ). In the last two reviews, which concerned PD, there were discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the relatively elderly patient population and ever increasing prevalence have led to higher socioeconomic burden of BCC [8].It was estimated by Chen et al that the average cost for NMSC care in US is $650 million each year [9]. Apart from age, mental disorders are thought to have an effect on non-melanoma skin cancer, especially BCC [10,11].…”
Section: Introductionmentioning
confidence: 99%